Business Strategy Formulation for "Remaja Peduli Lingkungan" in order to Increase Its Donor and Beneficiary Growth and Develop Its Sustainable Competitive Advantage - ., Wahyudin; Toha, Mohamad (The Indonesian Journal of Business Administration, 2019)
Abstract –  Remaja Peduli Lingkungan is a nonprofit organization that provides services for people who want to donate their money to people in need. The organizations today are facing several problems in carrying out their work. The competitive environment is now an inevitable threat to the organization. For that reason, Remaja Peduli Lingkungan needs to find the right strategy to boost its donors growth in order to enlarge their activities  to the community sustainably. Based on SWOT, the RPL strategy using diamond framework and new business model is designed. The study begins with analyzing the external environment using Porter 5 analysis, PESTEL analysis, and competitor analysis and internal analysis using a business model canvas analysis and value chain analysis. Based on internal and external analysis, obtained points of SWOT which indicate that the competitiveness of Remaja Peduli Lingkungan is currently still in temporary competitive advantage. In the analysis of business level strategy shows that the organization needs to remain in differentiation focus strategy. In the arena of analysis, differentiator, and partner, shows that organizations need to be more specific classify these items on both sides of the market. Implementation of the proposed strategy arranged on new business models canvas that can satisfy donors and beneficiaries.The changes in the proposed business model canvas adding items on each element of the business model canvas. The proposed implementation plan is designed for a period of three years considerating the environment rapid changing.Keywords: diamond strategy, business model canvas, sustainable competitive advantage